Negative electrode current collector and battery

JP7643238B2Active Publication Date: 2025-03-11TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021127110
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-03
Publication Date
2025-03-11
Estimated Expiration
2041-08-03

AI Technical Summary

Benefits of technology

【0006】 (1)本開示の一形態によれば、電解液を用いる電池の負極集電体が提供される。この負極集電体は、導電性を有する金属を主成分とする下地層と、前記下地層上に積層され、遷移金属を主成分とするバリア層と、前記バリア層上に積層され、前記遷移金属と、錫とが合金化された合金層と、前記合金層上に積層され、前記錫を主成分とするめっき層と、を備える。この形態によれば、負極集電体は、遷移金属を主成分とするバリア層と、遷移金属と錫とが合金化された合金層と、錫を主成分とするめっき層と、を備える。これにより、負極集電体を備えた負極において水素が発生することを抑制できるので、負極の外表面に水素が付着することを抑制できる。また、負極において水素が発生した場合に、負極集電体の外表面よりも内側に位置する合金層などの層において水素を保持できる。そのため、負極の外表面に水素が付着することを抑制できる。よって、負極集電体を備えた負極において水素が発生して、負極の外表面にその水素が付着することによって、電池の機能が低下することを抑制できる。 (2)上記形態であって、前記電解液は、アルカリ性の水系電解液であってもよい。この形態によれば、電解液がアルカリ性であるため、酸性や中性の電解液を用いる場合と比べて、電解液中により多くのヒドロキシイオンが存在する。このヒドロキシイオンと、負極活物質との反応により生じる電子が正極側に流れることで電池の放電機能を実現する。一方で、ヒドロキシイオンと負極活物質との反応により生じた電子が正極側に流れることなく、電解液中の水の還元反応に寄与することで、電解液中の水が酸化されて負極において水素が発生する場合が生じ得る。この場合においても、負極集電体が、バリア層と、合金層と、めっき層と、を備えることによって、負極集電体の外表面よりも内側に位置する合金層などの層において、発生した水素を保持できる。そのため、負極において水素が発生することを抑制できる。 (3)上記形態であって、前記遷移金属は、ニッケルと、鉄と、クロムと、ジルコニウムと、ランタンと、の少なくとも1つであってもよい。この形態によれば、負極において水素が発生した場合に、水素発生反応に係る交換電流密度が金よりも小さい遷移金属によって、バリア層を形成できる。そのため、この形態では、上記水素発生反応に係る交換電流密度が金よりも大きい遷移金属によってバリア層が形成される場合と比べて、負極における水素発生反応が起こりづらい。すなわち、負極において水素が発生することを抑制できる遷移金属によって、バリア層を形成できる。 (4)上記形態であって、前記バリア層の厚さは、2μm以上10μm以下であってもよい。この形態によれば、下地層をバリア層によって欠落無く覆うことができる。そのため、下地層がバリア層上に露出する可能性を低減できる。よって、下地層に含まれる金属が負極集電体の外表面側へ拡散する可能性を低減できる。 (5)上記形態であって、前記めっき層の厚さは、2μm以上5μm以下であってもよい。この形態によれば、合金層をめっき層によって欠落無く覆うことができる。そのため、負極において水素が発生した場合に、水素を保持する機能を有する合金層などの層が負極集電体の外表面に露出する可能性を低減できる。よって、負極において水素が発生することをさらに抑制できる。 (6)上記形態であって、前記バリア層は、前記遷移金属とは異なる異種元素であって、ホウ素と、アルミニウムと、リンと、チタンと、コバルトと、の少なくとも1つの異種元素を含有してもよい。この形態によれば、バリア層に異種元素が含有されることで、電解液中における負極活物質の溶解度を減少させるなどの付加的な機能を付与できる。 (7)上記形態であって、前記めっき層は、さらに、インジウムとビスマスとの少なくとも一方の元素を含有してもよい。この形態によれば、めっき層は、上記水素発生反応に係る交換電流密度が錫と同程度以下の金属を含有する。これにより、上記水素発生反応に係るめっき層の交換電流密度を小さくすることができる。よって、負極において水素が発生することをさらに抑制できる。 (8)本開示の他の形態によれば、電池が提供される。この電池は、上記形態に記載の負極集電体と、負極活物質とを含む負極と、正極集電体と、正極活物質とを含む正極と、前記負極と前記正極とを隔てるセパレータと、前記負極と、前記正極と、前記セパレータと、が配置された領域に収容された電解液と、を備える。この形態によれば、電池を構成する負極集電体は、遷移金属を主成分とするバリア層と、遷移金属と錫とが合金化された合金層と、錫を主成分とするめっき層と、を備える。これにより、負極集電体を備えた負極において水素が発生することを抑制できる。また、負極において水素が発生した場合に、負極集電体の外表面よりも内側に位置する合金層などの層において水素を保持できる。そのため、負極の外表面に水素が付着することを抑制できる。よって、負極の外表面に水素が付着することによって、電池の機能が低下することを抑制できる。 本開示は、上記の負極集電体、および、電池以外の種々の形態で実現することが可能である。例えば、負極集電体の製造方法や負極集電体を備えた電池の制御方法、その制御方法を実現するコンピュータプログラム、そのコンピュータプログラムを記録した一時的でない記録媒体等の形態で実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643238000001
    Figure 0007643238000001
  • Figure 0007643238000002
    Figure 0007643238000002
  • Figure 0007643238000003
    Figure 0007643238000003
Patent Text Reader

Abstract

To provide a technique capable of suppressing generation of hydrogen in a negative electrode provided with a negative electrode collector and suppressing sticking of hydrogen to the outer surface of the negative electrode.SOLUTION: The negative electrode collector for a battery using electrolyte comprises: a base layer mainly made of a conductive metal; a barrier layer mainly made of a transition metal and laminated on the base layer; an alloy layer having a transition metal and tin alloyed and laminated on the barrier layer; a plating layer mainly made of tin and laminated on the alloy layer; and an alloy layer having the transition metal of the barrier layer and the tin of the plating layer alloyed.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to negative electrode current collectors and battery technology. [Background technology]

[0002] Conventionally, a technique has been known for a negative electrode current collector in which an underlayer containing copper as a main component and a plating layer containing tin as a main component formed on the underlayer are fired to form an alloy layer between the underlayer and the plating layer (Patent Document 1). In this technique, the alloy layer is a compound composed of copper and tin. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2010-541183 Summary of the Invention [Problem to be solved by the invention]

[0004] In a battery having a negative electrode including a negative electrode current collector and a negative electrode active material arranged around the negative electrode current collector, when an aqueous electrolyte is used, hydrogen may be generated at the negative electrode. In this case, the generated hydrogen may adhere to the outer surface of the negative electrode, which may deteriorate the function of the battery. Therefore, a technology is desired that suppresses hydrogen generation at a negative electrode having a negative electrode current collector and adhesion of hydrogen to the outer surface of the negative electrode. [Means for solving the problem]

[0005] The present disclosure can be realized in the following forms. According to one embodiment of the present disclosure, there is provided a negative electrode current collector for a battery using an electrolyte, the negative electrode current collector comprising: a base layer mainly made of a conductive metal; a barrier layer mainly made of a transition metal laminated on the base layer; an alloy layer made of the transition metal and tin laminated on the barrier layer; and a plating layer mainly made of tin laminated on the alloy layer, the barrier layer containing at least one of boron, aluminum, phosphorus, titanium, and cobalt as a different element different from the transition metal. (2) According to another aspect of the present disclosure, there is provided a battery comprising: the anode current collector according to the above aspect, an anode including an anode active material, a cathode current collector, a cathode including a cathode active material, a separator separating the anode and the cathode, and an electrolyte solution contained in a region where the anode, the cathode, and the separator are arranged.

[0006] (1) According to one embodiment of the present disclosure, a negative electrode current collector for a battery using an electrolyte is provided. The negative electrode current collector includes a base layer mainly composed of a conductive metal, a barrier layer mainly composed of a transition metal laminated on the base layer, an alloy layer formed by alloying the transition metal and tin laminated on the barrier layer, and a plating layer mainly composed of tin laminated on the alloy layer. According to this embodiment, the negative electrode current collector includes a barrier layer mainly composed of a transition metal, an alloy layer formed by alloying the transition metal and tin, and a plating layer mainly composed of tin. This can suppress hydrogen generation in a negative electrode having a negative electrode current collector, and therefore hydrogen can be suppressed from adhering to the outer surface of the negative electrode. In addition, when hydrogen is generated in the negative electrode, hydrogen can be held in a layer such as an alloy layer located inside the outer surface of the negative electrode current collector. Therefore, hydrogen can be suppressed from adhering to the outer surface of the negative electrode. Therefore, hydrogen can be suppressed from being generated in a negative electrode having a negative electrode current collector, and the hydrogen can be adhered to the outer surface of the negative electrode, thereby suppressing a decrease in the function of the battery. (2) In the above embodiment, the electrolyte may be an alkaline aqueous electrolyte. According to this embodiment, since the electrolyte is alkaline, more hydroxy ions are present in the electrolyte than when an acidic or neutral electrolyte is used. Electrons generated by the reaction between the hydroxy ions and the negative electrode active material flow to the positive electrode side, thereby realizing the discharge function of the battery. On the other hand, there may be a case where the electrons generated by the reaction between the hydroxy ions and the negative electrode active material do not flow to the positive electrode side, but contribute to the reduction reaction of water in the electrolyte, causing the water in the electrolyte to be oxidized and hydrogen to be generated at the negative electrode. Even in this case, the negative electrode current collector includes a barrier layer, an alloy layer, and a plating layer, so that the generated hydrogen can be held in a layer such as an alloy layer located inside the outer surface of the negative electrode current collector. Therefore, the generation of hydrogen at the negative electrode can be suppressed. (3) In the above embodiment, the transition metal may be at least one of nickel, iron, chromium, zirconium, and lanthanum. According to this embodiment, when hydrogen is generated at the negative electrode, a barrier layer can be formed by a transition metal having an exchange current density related to the hydrogen generation reaction smaller than that of gold. Therefore, in this embodiment, the hydrogen generation reaction is less likely to occur at the negative electrode compared to a case where a barrier layer is formed by a transition metal having an exchange current density related to the hydrogen generation reaction larger than that of gold. In other words, a barrier layer can be formed by a transition metal that can suppress hydrogen generation at the negative electrode. (4) In the above embodiment, the barrier layer may have a thickness of 2 μm or more and 10 μm or less. According to this embodiment, the underlayer can be covered with the barrier layer without any gaps. This reduces the possibility that the underlayer is exposed on the barrier layer. This reduces the possibility that the metal contained in the underlayer diffuses to the outer surface side of the negative electrode current collector. (5) In the above embodiment, the thickness of the plating layer may be 2 μm or more and 5 μm or less. According to this embodiment, the alloy layer can be covered with the plating layer without any loss. Therefore, when hydrogen is generated in the negative electrode, the possibility that a layer such as the alloy layer having a function of retaining hydrogen is exposed on the outer surface of the negative electrode current collector can be reduced. Therefore, the generation of hydrogen in the negative electrode can be further suppressed. (6) In the above embodiment, the barrier layer may contain at least one of boron, aluminum, phosphorus, titanium, and cobalt as a different element different from the transition metal. According to this embodiment, the barrier layer contains a different element, which can impart an additional function such as reducing the solubility of the negative electrode active material in the electrolyte. (7) In the above embodiment, the plating layer may further contain at least one of indium and bismuth. According to this embodiment, the plating layer contains a metal whose exchange current density in the hydrogen generation reaction is equal to or less than that of tin. This makes it possible to reduce the exchange current density of the plating layer in the hydrogen generation reaction. Therefore, hydrogen generation at the negative electrode can be further suppressed. (8) According to another embodiment of the present disclosure, a battery is provided. The battery includes the negative electrode current collector described in the above embodiment, a negative electrode including a negative electrode active material, a positive electrode current collector, a positive electrode including a positive electrode active material, a separator separating the negative electrode and the positive electrode, and an electrolyte solution accommodated in an area where the negative electrode, the positive electrode, and the separator are arranged. According to this embodiment, the negative electrode current collector constituting the battery includes a barrier layer mainly composed of a transition metal, an alloy layer in which a transition metal and tin are alloyed, and a plating layer mainly composed of tin. This makes it possible to suppress hydrogen generation in a negative electrode including the negative electrode current collector. In addition, when hydrogen is generated in the negative electrode, hydrogen can be held in a layer such as an alloy layer located on the inside of the outer surface of the negative electrode current collector. Therefore, it is possible to suppress hydrogen from adhering to the outer surface of the negative electrode. Therefore, it is possible to suppress the deterioration of the function of the battery due to hydrogen adhering to the outer surface of the negative electrode. The present disclosure can be realized in various forms other than the above-mentioned negative electrode current collector and battery, for example, in the form of a method for manufacturing a negative electrode current collector, a method for controlling a battery including the negative electrode current collector, a computer program for implementing the control method, a non-transitory recording medium on which the computer program is recorded, etc. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a cross-sectional view illustrating the internal structure of the battery according to the embodiment. [Diagram 2] Enlarged view of the area in Figure 1. [Diagram 3] FIG. 13 shows the results of measurement by cyclic voltammetry using the produced negative electrode. [Figure 4] FIG. 4 is a diagram showing the conditions of a cycle durability test. [Diagram 5] FIG. 13 is a graph showing the results of a cycle durability test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] A. Embodiment: A-1. Battery composition: FIG. 1 is a schematic cross-sectional view showing the internal structure of a battery 1 according to this embodiment. FIG. 1 shows a view of the battery 1 cut along a plane along the longitudinal direction. In this embodiment, the battery 1 is a cylindrical nickel-zinc secondary battery in which a battery container body is sealed with an upper lid and a lower lid. The type and shape of the battery 1 are not limited to this. The battery 1 may be, for example, a nickel-cadmium storage battery. The shape of the battery 1 may be, for example, a laminated type, a rectangular type, or a pack type.

[0009] The battery 1 includes a negative electrode 2, a positive electrode 5, two separators C1 and C2, and an electrolyte 8. The negative electrode 2, the positive electrode 5, the two separators C1 and C2, and the electrolyte 8 are contained in the internal space of the battery 1 surrounded by the battery container body, the upper lid, and the lower lid. The negative electrode 2, the positive electrode 5, and the separators C1 and C2 are immersed in the electrolyte 8 in the internal space of the battery 1.

[0010] The negative electrode 2 includes a negative electrode current collector 20 and a negative electrode active material 28. The negative electrode current collector 20 has electrical conductivity. The negative electrode current collector 20 is electrically connected to a negative electrode terminal (not shown). Details of the negative electrode current collector 20 will be described later with reference to FIG. 2.

[0011] The negative electrode active material 28 contributes to an oxidation-reduction reaction in the negative electrode 2. In this embodiment, the negative electrode active material 28 is mainly composed of at least one of zinc (Zn) and an oxide of zinc. Specifically, for example, at least one of zinc (Zn) as an element and zinc oxide (ZnO) is used as the main component of the negative electrode active material 28. When the main component of the negative electrode active material 28 is zinc, for example, a zinc alloy containing zinc may be used. In the present disclosure, "main component" means "a proportion of more than 50 mass%."

[0012] The negative electrode active material 28 may further include additives such as a thickener, a binder, and other inorganic substances. The thickener is, for example, a cellulose-based polymer such as carboxymethyl cellulose (CMC). The binder is, for example, a fluorine-based resin such as polytetrafluoroethylene (PTFE). Note that the components and composition constituting the negative electrode active material 28 are not limited to these. The additives of the negative electrode active material 28 may be components having properties that enhance corrosion resistance, infiltration property, conductivity, and the like.

[0013] The positive electrode 5 includes a positive electrode collector 50 and a positive electrode active material 58. The positive electrode collector 50 has electrical conductivity. The positive electrode collector 50 is electrically connected to a positive electrode terminal (not shown). The positive electrode collector 50 is mainly composed of a metal having electrical conductivity. The metal having electrical conductivity used for the positive electrode collector 50 is, for example, any one of aluminum (Al), an alloy mainly composed of aluminum, nickel (Ni), and titanium (Ti). In this embodiment, the positive electrode collector 50 is mainly composed of nickel. Note that the positive electrode active material 58 may contain additives such as a thickener, a binder, and other inorganic substances, similar to the negative electrode active material 28.

[0014] The positive electrode active material 58 contributes to the oxidation-reduction reaction in the positive electrode 5. In this embodiment, the positive electrode active material 58 is mainly composed of nickel (Ni) or nickel hydroxide. The positive electrode active material 58 is, for example, nickel hydroxide (Ni(OH2)).

[0015] The separators C1 and C2 separate the negative electrode 2 and the positive electrode 5. Specifically, the separators C1 and C2 are walls provided between the negative electrode 2 and the positive electrode 5 to prevent an internal short circuit caused by contact between the negative electrode 2 and the positive electrode 5. In this embodiment, the first separator C1 is disposed on the negative electrode 2 side, and the second separator C2 is disposed on the positive electrode 5 side. The separators C1 and C2 have insulating properties and allow the electrolyte 8 to permeate. The separators C1 and C2 are, for example, porous films formed of polyolefins such as polypropylene (PP) and polyethylene (PE). The separators C1 and C2 may further include nonwoven fabrics formed of chemical fibers. The chemical fibers are, for example, any of polypropylene fibers, cellulose fibers, polyvinyl alcohol (PVA) fibers, and ethylene vinyl acetate (EVA) fibers.

[0016] The electrolyte 8 is a liquid having electrical conductivity. The electrolyte 8 is composed of either an aqueous electrolyte such as an alkaline aqueous solution or a non-aqueous electrolyte containing an organic electrolyte such as a lithium salt. In this embodiment, the electrolyte 8 is an alkaline aqueous electrolyte. The alkaline aqueous electrolyte as the electrolyte 8 contains an alkali metal hydroxide and water. The electrolyte 8 is, for example, an aqueous potassium hydroxide (KOH) solution, an aqueous sodium hydroxide (NaOH) solution, or an aqueous lithium hydroxide (LiOH) solution. The electrolyte 8 may be a mixture of a plurality of alkaline aqueous solutions. In this embodiment, the electrolyte 8 is an alkaline mixed aqueous solution containing potassium hydroxide as a main component, sodium hydroxide, and lithium hydroxide. The electrolyte 8 may further contain other inorganic additives and organic additives.

[0017] FIG. 2 is an enlarged view of a region R2 in FIG. 1. The negative electrode current collector 20 includes a base layer 210, a barrier layer 230, an alloy layer 250, and a plating layer 270. The negative electrode current collector 20 is a laminate in which these layers 210, 230, 250, and 270 are laminated. In the negative electrode current collector 20, the base layer 210, the barrier layer 230, the alloy layer 250, and the plating layer 270 are laminated in this order from the inside of the negative electrode current collector 20 toward the collector outer surface 20a, which is the outer surface of the negative electrode current collector 20. The base layer 210 is located at the center as the inside of the negative electrode current collector 20, which is a laminate. The barrier layer 230 is laminated on the base layer 210. The alloy layer 250 is laminated on the barrier layer 230. The plating layer 270 is laminated on the alloy layer 250 and forms the current collector outer surface 20a. That is, the plating layer 270 is provided at a position in contact with at least one of the electrolytic solution 8 and the negative electrode active material 28, as shown in FIG.

[0018] In the negative electrode 2, when an aqueous electrolyte solution is used as the electrolyte solution 8, a charge / discharge reaction occurs as shown in the following formula (1). Specifically, zinc (Zn) as the negative electrode active material 28 is converted into hydroxyl ions (OH - ) and is oxidized. This produces zinc hydroxide (Zn(OH)2) and releases electrons (e - In the following formula (1), the reaction from the left side to the right side is the discharge reaction. In the following formula (1), the reaction from the right side to the left side is the charge reaction. Zn+2OH - →Zn(OH)2+2e - Formula (1)

[0019] The underlayer 210 has a function as a current collector that collects electrons generated by the reaction of the above formula (1) and a function as a support that supports the other layers 230, 250, and 270. The underlayer 210 is a conductor mainly composed of a metal having electrical conductivity. In this embodiment, the underlayer 210 is mainly composed of copper (Cu). The thickness of the underlayer 210 may be any thickness within a range in which the underlayer 210 can function as a current collector and a support. The main component of the underlayer 210 is not limited to this. The underlayer 210 may be, for example, an alloy of copper and tin. The shape of the underlayer 210 may be, for example, a plate, foil, mesh, sponge, or fiber.

[0020] Here, in the case where an aqueous electrolyte solution is used as the electrolyte solution 8 in the negative electrode 2, hydrogen (H2) may be generated in the negative electrode 2 as shown in the following formula (2). Specifically, hydrogen is generated by contributing to a reaction that reduces water molecules (H2O) in the electrolyte solution 8 without flowing to the positive electrode 5 side in the electrons generated in the above formula (1). When hydrogen is generated in the negative electrode 2, the generated hydrogen may adhere to the outer surface 2a of the negative electrode 2, thereby deteriorating the function of the battery 1. Therefore, in this embodiment, in the negative electrode current collector 20 constituting the negative electrode 2, an alloy layer 250 is provided between the barrier layer 230 and the plating layer 270 in order to suppress the generation of hydrogen in the negative electrode 2. The alloy layer 250 is a layer obtained by alloying the barrier layer 230 as the first base material and the plating layer 270 as the second base material. By providing the barrier layer 230, the alloy layer 250, and the plating layer 270, the generation of hydrogen in the negative electrode 2 can be suppressed. This will be described in detail later. Incidentally, hydrogen may also be generated at the negative electrode 2 when a non-aqueous electrolyte solution that has absorbed moisture is used. 2H2O+2e - →H2+2OH - Formula (2)

[0021] The barrier layer 230 covers the underlayer 210, thereby suppressing the diffusion of the conductive metal (copper in this embodiment) contained in the underlayer 210 toward the current collector outer surface 20a. The barrier layer 230 also serves as a first base material for forming the alloy layer 250. The barrier layer 230 covers the entire surface of the underlayer 210 without any missing parts. The barrier layer 230 is formed on the underlayer 210 by, for example, electroplating. The barrier layer 230 may be formed on the underlayer 210 by other methods such as hot-dip plating, vapor plating, or chemical plating.

[0022] The barrier layer 230 preferably has a thickness that does not allow copper contained in the underlayer 210 to diffuse to the current collector outer surface 20a side where the electrolytic solution 8 is present. Specifically, the thickness of the barrier layer 230 is preferably 2 μm or more and 10 μm or less. By setting the thickness of the barrier layer 230 to 2 μm or more, the underlayer 210 can be covered with the barrier layer 230 without any loss. In addition, the upper limit of the thickness of the barrier layer 230 is set to 10 μm in consideration of operability and cost when performing electroplating to cover the underlayer 210 with the barrier layer 230. However, the thickness of the barrier layer 230 is not limited to this. The thickness of the barrier layer 230 may be, for example, more than 10 μm.

[0023] The barrier layer 230 is mainly composed of a transition metal. In this embodiment, the transition metal is, for example, at least one of nickel (Ni), iron (Fe), chromium (Cr), zirconium (Zr), and lanthanum (La). The transition metal mainly composed of the barrier layer 230 preferably satisfies the following condition (i) in order to protect the underlayer 210 mainly composed of copper. The transition metal mainly composed of the barrier layer 230 preferably satisfies the following condition (ii) in order to suppress the generation of hydrogen generated by the reaction formula (2) above. In order to suppress the generation of hydrogen in the negative electrode 2, a method of making the reaction that generates hydrogen as shown in the above formula (2) (hereinafter, hydrogen generation reaction) less likely to occur is considered. The following condition (ii) is an example of a condition for realizing the method of making the hydrogen generation reaction shown in the above formula (2) less likely to occur. (i) A transition metal that can suppress the diffusion of copper from the underlayer 210 to the plating layer 270 forming the current collector outer surface 20a when the underlayer 210 containing copper as a main component is covered with the barrier layer 230. (ii) A transition metal that has a smaller exchange current density than gold (Au) in the hydrogen evolution reaction shown in the above formula (2).

[0024] As shown in the above condition (i), in order to suppress the diffusion of copper, which is the main component of the underlayer 210, toward the plating layer 270 forming the current collector outer surface 20a, it is preferable to select a transition metal suitable for the barrier layer 230 covering the underlayer 210. In order to suppress the diffusion of copper contained in the underlayer 210 toward the plating layer 270, the transition metal suitable for use in the plating layer 270 is, for example, either nickel (Ni) or iron (Fe). In addition, in order to suppress the diffusion of copper contained in the underlayer 210 toward the plating layer 270, the transition metal not suitable for use in the plating layer 270 is, for example, either indium (In), tin (Sn), or bismuth (Bi).

[0025] As shown in the above condition (ii), it is preferable to select a transition metal in which the hydrogen generation reaction shown in the above formula (2) is unlikely to occur as the main component of the barrier layer 230. In this embodiment, transition metals are divided into three groups according to the magnitude of the exchange current density related to the hydrogen generation reaction shown in the above formula (2). Specifically, a group having an exchange current density related to the hydrogen generation reaction shown in the above formula (2) greater than that of gold is defined as the first group, and a group having an exchange current density related to the hydrogen generation reaction shown in the above formula (2) smaller than that of gold is defined as the second and third groups. The second group is a transition metal whose exchange current density related to the hydrogen generation reaction shown in the above formula (2) is smaller than that of gold, but whose exchange current density related to the hydrogen generation reaction shown in the above formula (2) is greater than that of metals belonging to the third group. Note that some of the elements belonging to the third group do not fall under the category of transition metals, but will be described here in advance because they will be necessary in the plating layer 270 when described later.

[0026] The transition metals belonging to the first group are, for example, any of rhodium (Rh), rhenium (Re), iridium (Ir), and platinum (Pt). The transition metals belonging to the second group are, for example, any of nickel (Ni), iron (Fe), and cobalt (Co). The metals belonging to the third group are, for example, any of indium (In), tin (Sn), bismuth (Bi), and titanium (Ti). The transition metals belonging to the first group have a higher exchange current density related to the hydrogen generation reaction shown in the above formula (2) than gold, and are relatively higher than the transition metals belonging to the second and third groups, so that the reaction shown in the above formula (2) may occur easily. On the other hand, the transition metals belonging to the second and third groups have a lower exchange current density related to the hydrogen generation reaction shown in the above formula (2) than the metals belonging to the first group, so that the reaction shown in the above formula (2) is less likely to occur than when the transition metals of the first group are used. Therefore, when the transition metals belonging to the second and third groups are used as the main component of the barrier layer 230, the possibility of the hydrogen evolution reaction shown in the above formula (2) occurring can be reduced. Therefore, as shown in the above condition (ii), it is preferable to select, as the main component of the barrier layer 230, a transition metal belonging to the second and third groups, which has a smaller exchange current density related to the hydrogen evolution reaction shown in the above formula (2) than gold.

[0027] For the above reasons, in this embodiment, nickel is used as the transition metal that satisfies the above condition (i) and the above condition (ii).

[0028] The barrier layer 230 may contain at least one of boron, aluminum, phosphorus, titanium, and cobalt, which is a different element from the transition metal that is the main component of the barrier layer 230. By containing a different element such as phosphorus in the barrier layer 230, an additional function such as reducing the solubility of the negative electrode active material 28 in the electrolyte solution 8 can be imparted.

[0029] The plating layer 270 is formed on the current collector outer surface 20a to protect the inner layer, for example, the alloy layer 250. The plating layer 270 further serves as a second base material for forming the alloy layer 250. The plating layer 270 covers the entire surface of the barrier layer 230 without any missing parts. The surface of the barrier layer 230 referred to here refers to the surface of the barrier layer 230 opposite to the surface in contact with the base layer 210. The plating layer 270 is formed on the barrier layer 230 by, for example, electroplating. The plating layer 270 may be formed on the barrier layer 230 by other methods, such as hot-dip plating, vapor plating, or chemical plating.

[0030] The plating layer 270 is preferably thick enough to protect the alloy layer 250 and to obtain a desired thickness of the alloy layer 250 when the plating layer 270 and the barrier layer 230 are alloyed. Specifically, the thickness of the plating layer 270 is preferably 2 μm or more and 5 μm or less. If the plating layer 270 is thin, for example, less than 2 μm, pinholes may occur when covering the surface of the barrier layer 230, or the plating layer 270 formed on the barrier layer 230 may become uneven on the surface of the barrier layer 230. As a result, the barrier layer 230 may be exposed so as to come into contact with the electrolytic solution 8. In addition, the upper limit of the thickness of the plating layer 270 is set to 5 μm in consideration of operability and cost when performing electroplating to cover the barrier layer 230 with the plating layer 270. The thickness of the plating layer 270 is not limited to this. The thickness of the plating layer 270 may be, for example, more than 10 μm.

[0031] The plating layer 270 is mainly composed of tin (Sn). There are four reasons for selecting tin as the main component of the plating layer 270. First, the inventors of the present application found that hydrogen generation in the negative electrode 2 can be suppressed by providing the alloy layer 250, which is an alloy of nickel and tin, on the negative electrode current collector 20. Second, as described above, tin has a small exchange current density related to the hydrogen generation reaction shown in the above formula (2), and is less likely to generate hydrogen. Third, tin is widely used as a plating material, and is excellent in the flexibility of the coating formed on the target object (in this embodiment, the barrier layer 230 and the alloy layer 250) and in the operability in plating work. Fourth, the corrosion resistance of the target object can be improved by covering the target object with tin. For the above reasons, in this embodiment, tin is used as the main component of the plating layer 270.

[0032] The plating layer 270 may contain at least one of indium (In) and bismuth (Bi) as an additive. Indium and bismuth are transition metals belonging to the third group, which have a lower exchange current density for the hydrogen evolution reaction shown in the above formula (2) than gold. Therefore, the exchange current density of the plating layer 270 can be made smaller than when the plating layer 270 does not contain at least one of indium and bismuth. Indium and bismuth can generally contribute to improving the corrosion resistance of the negative electrode active material 28.

[0033] The alloy layer 250 contributes to suppressing hydrogen generation in the negative electrode 2. Specifically, the negative electrode current collector 20 retains hydrogen generated on the outer surface 2a of the negative electrode 2 in layers such as the alloy layer 250 located on the inner side of the current collector outer surface 20a. The alloy layer 250 is formed by maintaining the laminated state in which the underlayer 210, the barrier layer 230, and the plating layer 270 are laminated in this order from the inner side toward the current collector outer surface 20a for a predetermined time. Specifically, when the laminated state is maintained, nickel, which is the main component of the barrier layer 230, and tin, which is the main component of the plating layer 270, are alloyed by natural diffusion. As a result, the alloy layer 250 is formed between the barrier layer 230 and the plating layer 270. In this embodiment, the alloy layer 250 is an alloy of nickel and tin.

[0034] When forming the alloy layer 250, the plating layer 270 may be heat-treated in a laminated state. For example, the plating layer 270 is heated at 220° C. for 10 minutes as the heat treatment. The heat treatment for the plating layer 270 is a so-called reflow treatment. By performing the heat treatment for the plating layer 270, the plating layer 270 can be made uniform. This can prevent the plating layer 270 from becoming non-uniform or having pinholes. Therefore, the possibility that the alloy layer 250 formed between the barrier layer 230 and the plating layer 270 is exposed to the collector outer surface 20a of the negative electrode current collector 20 can be reduced. Note that the conditions such as the heating time and heating temperature in the heat treatment performed on the plating layer 270 are not limited to those described above. The heating temperature in the heat treatment may be lower than 220° C. In addition, the heating time in the heat treatment may be longer or shorter than 10 minutes.

[0035] According to the above embodiment, the negative electrode current collector 20 includes the underlayer 210, the barrier layer 230 mainly composed of a transition metal, the alloy layer 250 in which the transition metal of the barrier layer 230 and the tin of the plating layer 270 are alloyed, and the plating layer 270 mainly composed of tin. The underlayer 210, the barrier layer 230, the alloy layer 250, and the plating layer 270 are laminated in this order from the inside toward the current collector outer surface 20a. At this time, by including at least the barrier layer 230, the alloy layer 250, and the plating layer 270 in the negative electrode current collector 20, it is possible to suppress the generation of hydrogen in the negative electrode 2. In addition, when hydrogen is generated in the negative electrode 2, the hydrogen can be held in layers such as the alloy layer 250 located on the inside of the current collector outer surface 20a. Therefore, it is possible to suppress the attachment of hydrogen to the outer surface 2a of the negative electrode 2. Therefore, it is possible to suppress the deterioration of the function of the battery 1 due to the attachment of hydrogen to the outer surface 2a of the negative electrode 2.

[0036] According to the above embodiment, an alkaline aqueous electrolyte is used as the electrolyte 8. In this case, the electrolyte 8 of the present embodiment contains more hydroxy ions than an electrolyte whose liquid property is acidic or neutral. The electrons generated by the reaction between the hydroxy ions and the negative electrode active material 28 shown in the above formula (1) flow to the positive electrode side, and the battery 1 realizes a discharge function. On the other hand, the electrons generated by the reaction between the hydroxy ions and the negative electrode active material 28 may not flow to the positive electrode side, but may contribute to the reduction reaction of water in the electrolyte shown in the above formula (2), causing the reaction shown in the above formula (2) to occur, and hydrogen may be generated in the negative electrode 2. Even in this case, the negative electrode current collector 20 includes at least the barrier layer 230, the alloy layer 250, and the plating layer 270, so that hydrogen can be retained in layers such as the alloy layer 250 located on the inner side of the current collector outer surface 20a. Therefore, hydrogen generation in the negative electrode 2 can be suppressed. Therefore, the deterioration of the function of the battery 1 caused by hydrogen adhering to the outer surface 2a of the negative electrode 2 can be suppressed.

[0037] According to the embodiment, the barrier layer 230 is mainly composed of at least one transition metal selected from nickel, iron, chromium, zirconium, and lanthanum. In this case, the water in the electrolyte 8 is oxidized as shown in the above formula (2) due to electrons generated by the reaction shown in the above formula (1), and hydrogen is generated. When hydrogen is generated in the negative electrode 2, the barrier layer 230 can be formed by a transition metal having an exchange current density related to the hydrogen generation reaction smaller than that of gold. Therefore, the hydrogen generation reaction shown in the above formula (2) is less likely to occur compared to when the barrier layer 230 is formed by a transition metal having an exchange current density related to the hydrogen generation reaction larger than that of gold. Therefore, the barrier layer 230 can be formed by a transition metal that can suppress the generation of hydrogen in the negative electrode 2.

[0038] In the above embodiment, the thickness of the barrier layer 230 is set to 2 μm or more and 10 μm or less. In this way, the base layer 210 can be covered with the barrier layer 230 without any gaps. This reduces the possibility that the base layer 210 is exposed on the barrier layer 230. This reduces the possibility that the metal contained in the base layer 210 diffuses toward the current collector outer surface 20a.

[0039] In the above embodiment, the thickness of the plating layer 270 is set to 2 μm or more and 5 μm or less. In this way, the alloy layer 250 can be covered with the plating layer 270 without any loss. Therefore, when hydrogen is generated in the negative electrode 2, the possibility that layers such as the alloy layer 250 having a function of retaining hydrogen are exposed to the current collector outer surface 20a can be reduced. Therefore, the generation of hydrogen in the negative electrode 2 can be more reliably suppressed.

[0040] Furthermore, according to the above embodiment, the barrier layer 230 may contain at least one of boron, aluminum, phosphorus, titanium, and cobalt, which is a different element from the transition metal that is the main component of the barrier layer 230. By containing a different element such as phosphorus in the barrier layer 230, an additional function such as reducing the solubility of the negative electrode active material 28 in the electrolyte solution 8 can be imparted.

[0041] According to the above embodiment, the plating layer 270 can be configured to include at least one of indium and bismuth. That is, the plating layer 270 contains a metal whose exchange current density in the hydrogen generation reaction shown in the above formula (2) is smaller than that of gold and is equal to or smaller than that of tin. This can reduce the exchange current density of the plating layer 270 in the hydrogen generation reaction shown in the above formula (2). Therefore, hydrogen generation in the negative electrode 2 can be further suppressed.

[0042] Furthermore, according to the above embodiment, in a laminated state in which the base layer 210, the barrier layer 230, and the plating layer 270 are laminated in this order from the inside toward the current collector outer surface 20a, a heat treatment is performed on the plating layer 270. This makes it possible to make the plating layer 270 uniform. That is, it is possible to reduce the possibility that the plating layer 270 will become non-uniform or that pinholes will occur. Therefore, in a state in which the alloy layer 250 is formed between the barrier layer 230 and the plating layer 270, it is possible to reduce the possibility that the alloy layer 250 will be exposed to the current collector outer surface 20a.

[0043] A-2. Experimental Examples: A-2-1. Experimental Example 1: On the premise of the configuration described above, samples X1 to X4 as the negative electrode 2 of this embodiment and sample Y1 as a comparative example were produced. In this experiment, the sample Y1 as a comparative example was compared with the samples X1 to X4 of this embodiment to confirm the difference in hydrogen generation in the negative electrode 2 depending on the presence or absence of the barrier layer 230, the alloy layer 250, and the plating layer 270. The sample Y1 as a comparative example differs from the samples X1 to X4 in the configuration of the negative electrode current collector 20. Specifically, the negative electrode current collector 20 of sample Y1 does not include the barrier layer 230 and the plating layer 270. As a result, the negative electrode current collector 20 of sample Y1 does not include the barrier layer 230, the alloy layer 250, and the plating layer 270.

[0044] Sample X1 was produced as follows. From the viewpoint of electrical conductivity and workability, a punching metal formed of oxygen-free copper (C1020) was used for the underlayer 210. The barrier layer 230 was formed on the underlayer 210 without any defects. The thickness of the barrier layer 230 was set to 2 μm. Next, the plating layer 270 was formed on the barrier layer 230 without any defects. The thickness of the plating layer 270 was set to 3 μm. Next, in a laminated state in which the underlayer 210, the barrier layer 230, and the plating layer 270 were laminated in this order from the inside toward the collector outer surface 20a, the laminated state was maintained for a predetermined time. As a result, an alloy layer 250 was formed between the barrier layer 230 and the plating layer 270. A laminate in which these layers 210, 230, 250, and 270 were laminated was used as the negative electrode current collector 20.

[0045] In producing the negative electrode active material 28, powdered zinc oxide, powdered zinc, carboxymethyl cellulose, and a dispersion liquid in which polytetrafluoroethylene was dispersed were mixed in a weight ratio of 90:10:1:2 to obtain a first mixed liquid. A suitable amount of a solution in which water and isopropanol (IPA) were mixed in a weight ratio of 1:1 was dropped into the first mixed liquid to obtain a second mixed liquid. The second mixed liquid was stirred for 15 minutes using a rotation-revolution mixer manufactured by Thinky Corporation to obtain a slurry ink, which was used as the negative electrode active material 28.

[0046] To prepare the negative electrode 2, 1 cm 2 A negative electrode active material 28 was applied to the negative electrode current collector 20 so that about 100 mg of the negative electrode active material 28 was applied to the negative electrode current collector 20, thereby obtaining a negative electrode composite material. The negative electrode composite material was dried at 80° C. for 2 hours, and then pressed at a linear pressure of 0.75 t using a roll press machine manufactured by Takumi Giken Co., Ltd. to obtain a negative electrode 2.

[0047] The first separator C1 was formed from a polypropylene porous film and a mixed nonwoven fabric of polyvinyl alcohol fiber and cellulose fiber. After a copper foil having a thickness of 120 μm was welded to one end of the negative electrode 2 by a resistance welding machine, the negative electrode 2 was wrapped with the first separator C1 to form a negative electrode-separator composite.

[0048] The positive electrode current collector 50 was made of "Celmet (registered trademark)" manufactured by Sumitomo Electric Industries, Ltd., which is a porous metal mainly composed of nickel. A positive electrode terminal was welded to the positive electrode 5 composed of the positive electrode current collector 50 and nickel hydroxide as the positive electrode active material 58, and the positive electrode composite was obtained by stacking them. The second separator C2 was made of nonwoven fabric. The positive electrode composite was welded and embedded in the second separator C2 to form a positive electrode-separator composite.

[0049] The negative electrode-separator composite and the positive electrode-separator composite were placed in a space formed by the battery container body and the bottom lid, and a predetermined amount of electrolyte 8 was added. The electrolyte 8 was an alkaline mixed aqueous solution containing potassium hydroxide aqueous solution as the main component, sodium hydroxide aqueous solution, and lithium hydroxide aqueous solution. This resulted in the negative electrode-separator composite and the positive electrode-separator composite being immersed in the electrolyte 8. The container was then sealed with the top lid to obtain sample X1.

[0050] Sample X2 is a sample obtained by subjecting the plating layer 270 of the negative electrode current collector 20 of Sample X1 to a heat treatment. In Sample X2, the plating layer 270 was subjected to a heat treatment in a laminated state in which the underlayer 210, the barrier layer 230, and the plating layer 270 were laminated in this order from the inside toward the current collector outer surface 20a. Specifically, in the laminated state, the plating layer 270 was heated at 220°C for 10 minutes to melt the plating layer 270. Thereafter, the heated plating layer 270 was quenched to obtain Sample X2. The other components of Sample X2 and the manufacturing method of Sample X2 were the same as those of Sample X1.

[0051] Sample X3 is a sample in which the barrier layer 230 in the negative electrode current collector 20 of Sample X1 contains phosphorus as a different element different from the main component of the barrier layer 230. The other components of Sample X3 and the method for producing Sample X3 are the same as those of Sample X1.

[0052] Sample X4 is a sample in which the thickness of the barrier layer 230 and the thickness of the plating layer 270 in the negative electrode current collector 20 of Sample X1 are each reduced. In Sample X4, the thickness of the barrier layer 230 is 1 μm, and the thickness of the plating layer 270 is 2 μm. The other components of Sample X4 and the manufacturing method of Sample X4 are the same as those of Sample X1.

[0053] Sample Y1 as a comparative example is a sample that does not have the barrier layer 230, the alloy layer 250, and the plating layer 270 provided on the negative electrode current collector 20 of Sample X1. The other components of Sample Y1 and the manufacturing method of Sample Y1 are the same as those of Sample X1.

[0054] Fig. 3 is a diagram showing the measurement results by cyclic voltammetry using the produced negative electrode 2. Fig. 3 shows the measurement results of samples X1 to X4 and sample Y1 as a comparative example.

[0055] Cyclic voltammetry is a basic measurement technique in the electrochemistry field in which an electrode potential is repeatedly swept and a response current during the sweep is measured. In the measurement according to FIG. 3, any one of the samples X1 to X4, Y1, a nickel counter electrode, and a mercury-mercury oxide electrode as a reference electrode were placed in an electrochemical cell. A 6 mol / L aqueous potassium hydroxide solution was added to this electrochemical cell as an electrolyte 8. In this state, a reciprocating sweep was performed between −1.2 V and −1.9 V with respect to the potential of the reference electrode (SHE ratio +0.10 V). That is, in the measurement according to FIG. 3, a negative sweep from −1.2 V to −1.9 V and a positive sweep from −1.9 V to −1.2 V with respect to the potential of the reference electrode (SHE ratio +0.10 V) were performed once each.

[0056] The horizontal axis of FIG. 3 represents the potential of the reference electrode. In FIG. 3, the unit of the potential of the reference electrode is [V]. The vertical axis of FIG. 3 represents the response current value with respect to the potential. In FIG. 3, the unit of the response current value is [mA]. ​​The graph in FIG. 3 is a so-called cyclic voltammogram, which represents the transition of the change in the response current value at a specific potential. In FIG. 3, the average value of the positive sweep and the negative sweep between -1.2V and -1.9V is shown as one graph. In the cyclic voltammogram, a peak representing the potential difference occurs near the redox potential. In FIG. 3, the peak formed in the direction in which the response current value becomes negative is a reduction wave generated by the fluctuation of the reduction side current. The peak formed in the direction in which the response current value becomes positive is an oxidation wave generated by the fluctuation of the oxidation side current.

[0057] In FIG. 3, in the sample Y1 in which the barrier layer 230, the alloy layer 250, and the plating layer 270 are not provided on the negative electrode current collector 20, the reduction-side current is greatly reduced when the potential of the reference electrode becomes approximately −1.9 V. In contrast, in the sample X1 in which the barrier layer 230, the alloy layer 250, and the plating layer 270 are provided on the negative electrode current collector 20, the reduction-side current is approximately −3.0 mA when the potential of the reference electrode becomes −1.9 V. That is, the reduction-side current of the sample X1 is smaller than that of the sample Y1 when the potential of the reference electrode becomes −1.9 V. In other words, the reduction wave of the sample X1 is smaller than that of the sample Y1 when the potential of the reference electrode becomes −1.9 V. In this embodiment, the point when the potential of the reference electrode becomes approximately −1.9 V corresponds to the oxidation-reduction potential of the hydrogen generation reaction shown in the above formula (2).

[0058] Here, the magnitude of the reduction wave is proportional to the amount of electrons supplied to the negative electrode 2. That is, when the reduction wave is large, more electrons are supplied to the negative electrode 2, and the reduction reaction proceeds actively. On the other hand, as the reduction wave is small, fewer electrons are supplied to the negative electrode 2, and the reduction reaction is suppressed. Therefore, compared to sample Y1, sample X1 is able to suppress the generation of hydrogen in the negative electrode 2 including the negative electrode current collector 20. That is, when the barrier layer 230, the alloy layer 250, and the plating layer 270 are provided in the negative electrode current collector 20 constituting the negative electrode 2, the generation of hydrogen in the negative electrode 2 can be suppressed.

[0059] 3, in sample X1, a fluctuation in the oxidation-side current is observed and an oxidation wave is formed when the potential of the reference electrode is in the vicinity of −1.5 to −1.4 V. In contrast, in sample Y1, no fluctuation in the oxidation-side current is observed and an oxidation wave is not formed when the potential of the reference electrode is in the vicinity of −1.5 to −1.4 V.

[0060] The size of the oxidation wave is proportional to the amount of electrons lost from the negative electrode 2 side. Specifically, when the oxidation wave is formed, an oxidation reaction occurs on the negative electrode 2 side as a reaction in which electrons are lost. Therefore, even if hydrogen is generated on the negative electrode 2, it is considered that the sample X1 can suppress the adhesion of hydrogen to the outer surface 2a of the negative electrode 2 due to the oxidation reaction that occurs when the potential of the reference electrode becomes approximately -1.5 to -1.4 V. The oxidation reaction that occurs when the potential of the reference electrode becomes approximately -1.5 to -1.4 V is considered to be, for example, a reaction in which hydrogen is oxidized to generate water, as shown in the following formula (3). It can also be said that a layer such as the alloy layer 250 located inside the current collector outer surface 20a has an oxidation-reduction ability. 2H2+O2→2H2O Formula (3)

[0061] It is considered that the larger the oxidation wave is at the time when the potential of the reference electrode is in the vicinity of -1.5 to -1.4 V, the more actively the oxidation reaction shown in the above formula (3) proceeds. In other words, it is considered that the larger the oxidation wave is, the greater the proportion of hydrogen generated by the reaction formula (2) above that is oxidized to produce water, and therefore the amount of hydrogen attached to the outer surface 2a of the negative electrode 2 decreases.

[0062] In addition, by providing the barrier layer 230, the alloy layer 250, and the plating layer 270 in the negative electrode current collector 20, it is considered that the alloy layer 250 and other layers located inside the current collector outer surface 20a function like a hydrogen storage alloy. Specifically, the negative electrode current collector 20 absorbs hydrogen generated in the negative electrode 2 to form a metal hydride. In other words, the alloy layer 250 and other layers located inside the current collector outer surface 20a hold hydrogen. In this way, it is possible that hydrogen generation in the negative electrode 2 is suppressed by storing hydrogen in the form of a metal hydride in the negative electrode current collector 20.

[0063] It is considered that the larger the oxidation wave is at the time when the potential of the reference electrode is in the vicinity of -1.5 to -1.4 V, the more actively the formation of metal hydride progresses. In other words, it is considered that the larger the oxidation wave is, the greater the amount of hydrogen absorbed in layers such as the alloy layer 250 located inside the current collector outer surface 20a, and the less hydrogen adheres to the outer surface 2a of the negative electrode 2. It is also possible that hydrogen held in layers such as the alloy layer 250 located inside the current collector outer surface 20a is oxidized by the reaction formula (3) above.

[0064] In addition, in the heat-treated sample X2, the reduction-side current at the time when the potential of the reference electrode becomes -1.9V is about -2.5mA. That is, at the time when the potential of the reference electrode becomes -1.9V, the reduction-side current of the sample X2 is smaller than that of the sample Y1 as a comparative example, similar to the sample X1. At the time when the potential of the reference electrode becomes -1.9V, the reduction-side current of the sample X2 is smaller than that of the sample X1. As shown in FIG. 3, in the sample X2, at the time when the potential of the reference electrode becomes about -1.5 to -1.4V, the oxidation-side current fluctuates and an oxidation wave is formed, similar to the sample X1. At this time, the oxidation wave of the sample X2 has a larger peak than that of the sample X1. From this, by performing a heat treatment on the plating layer 270 in the process of forming the alloy layer 250, the generation of hydrogen in the negative electrode 2 can be further suppressed.

[0065] In the sample X3 in which phosphorus is added to the barrier layer 230, the reduction-side current at the time when the potential of the reference electrode becomes −1.9 V is about −2.4 mA. That is, at the time when the potential of the reference electrode becomes −1.9 V, the reduction-side current of the sample X3 is smaller than that of the sample Y1 as a comparative example, similar to the sample X1. Also, at the time when the potential of the reference electrode becomes −1.9 V, the reduction-side current of the sample X3 is smaller than that of the sample X1 and the sample X2. As shown in FIG. 3, in the sample X3, at the time when the potential of the reference electrode becomes about −1.5 to −1.4 V, a fluctuation in the oxidation-side current is observed and an oxidation wave is formed, similar to the sample X1. From this, by including phosphorus as a different element different from the main component of the barrier layer 230 in the barrier layer 230, the generation of hydrogen in the negative electrode 2 can be further suppressed.

[0066] In sample X4, in which the thickness of the barrier layer 230 and the thickness of the plating layer 270 are thinner than those of sample X1, the reduction-side current at the time when the potential of the reference electrode is about -1.9 V is about -4.5 mA. That is, at the time when the potential of the reference electrode is about -1.9 V, the reduction-side current of sample X4 is smaller than that of sample Y1 as a comparative example, but is larger than that of samples X1 to X3. In addition, at the time when the potential of the reference electrode is about -1.9 V, the reduction-side current value of sample X4 is closer to that of sample Y1 than that of samples X1 to X3. From this, even when the thickness of the barrier layer 230 is 1 μm and the thickness of the plating layer 270 is 2 μm, the generation of hydrogen in the negative electrode 2 can be suppressed by providing the barrier layer 230, the alloy layer 250, and the plating layer 270 in the negative electrode current collector 20. On the other hand, compared with a case where the barrier layer 230 is 2 μm thick and the plating layer 270 is 3 μm thick, when the barrier layer 230 is 1 μm thick and the plating layer 270 is 2 μm thick, it is difficult to obtain the effect of suppressing hydrogen generation in the negative electrode 2. Therefore, it is more preferable that the barrier layer 230 is 2 μm thick or more and the plating layer 270 is 3 μm thick or more.

[0067] A-2-2. Experimental Example 2: Furthermore, to compare the performance of the battery 1, a cycle endurance test was conducted on the samples X1 to X4 and the sample Y1. FIG. 4 is a diagram showing the conditions of the cycle endurance test. In this test, the samples X1 to X4 as the battery 1 of this embodiment and the sample Y1 as a comparative example were repeatedly charged and discharged, and the performance of the samples X1 to X4 and Y1 was evaluated by measuring the number of charge / discharge cycles until the functions of the samples X1 to X4 and Y1 deteriorated. In the initial state before the start of this test, the samples X1 to X4 and Y1 had a full charge capacity of 120 mAh and a remaining capacity (SOC) of 100%.

[0068] As shown in FIG. 4, in this test, the charging step and the discharging step were repeatedly performed. Between each of the charging and discharging steps, a waiting time of 5 minutes was provided during which neither the charging step nor the discharging step was performed. In this test, one cycle consisted of a charging step, a first waiting time after the charging step and before the discharging step, and a discharging step, and a second waiting time after the discharging step and before the charging step as a time point at which the next cycle was started. The charging step was performed by a CC-CV method that combines constant current charging and constant voltage charging. Specifically, in the charging step, a current of 1C was supplied to samples X1 and Y1 until the voltage reached 2.00V, and then a current of 60mA was supplied while maintaining the voltage at 2.00V. When a predetermined termination condition indicating the completion of charging was reached, the charging step in this cycle was terminated. The discharging step was performed by a constant current discharge (CC) method. Specifically, in the discharging step, a current of 1C was supplied to samples X1 and Y1 until the voltage reached 1.1V.

[0069] FIG. 5 is a diagram showing the results of a cycle durability test. FIG. 5 shows the test results for samples X1 to X4 as the battery 1 of this embodiment and sample Y1 as a comparative example. In this test, the number of cycles until the battery capacity ratio of samples X1 to X4 and Y1 decreased to 30% was measured, assuming that the battery capacity at the start was 100%, and the time point at which the charge / discharge function of samples X1 to X4 and Y1 decreased was determined. As shown in FIG. 5, sample Y1, which does not have a barrier layer 230, an alloy layer 250, and a plating layer 270 on the negative electrode current collector 20, reached a battery capacity ratio of 30% at 25 cycles. In contrast, sample X1, which has a barrier layer 230, an alloy layer 250, and a plating layer 270 on the negative electrode current collector 20, reached a battery capacity ratio of 30% at 154 cycles. That is, by providing the barrier layer 230, the alloy layer 250, and the plating layer 270 in the negative electrode current collector 20, it is possible to increase the number of cycles until the battery capacity ratio decreases to 30%, thereby suppressing the deterioration of the function of the battery 1.

[0070] In the heat-treated sample X2, the battery capacity ratio reached 30% after 160 cycles. This shows that by subjecting the plating layer 270 in the negative electrode current collector 20 to a heat treatment, the number of cycles until the battery capacity ratio decreases to 30% can be further increased.

[0071] In sample X3, in which phosphorus was added to the barrier layer 230, the battery capacity ratio reached 30% at 255 cycles. This shows that by including a different element in the barrier layer 230, the number of cycles until the battery capacity ratio decreases to 30% can be further increased.

[0072] In sample X4, in which the thickness of the barrier layer 230 and the thickness of the plating layer 270 are thinner than those of sample X1, the battery capacity ratio reaches 30% after 60 cycles. From this, even when the thickness of the barrier layer 230 is 1 μm and the thickness of the plating layer 270 is 2 μm, the number of cycles until the battery capacity ratio drops to 30% can be increased by providing the barrier layer 230, the alloy layer 250, and the plating layer 270. On the other hand, the increase in the number of cycles of sample X4 compared to sample Y1 is smaller than those of samples X1 to X3. That is, compared to when the thickness of the barrier layer 230 is 2 μm and the thickness of the plating layer 270 is 3 μm, it is difficult to increase the number of cycles compared to sample Y1 when the thickness of the barrier layer 230 is 1 μm and the thickness of the plating layer 270 is 2 μm. Therefore, it is more preferable that the thickness of the barrier layer 230 is 2 μm or more and the thickness of the plating layer 270 is 3 μm or more.

[0073] B. Other embodiments: In the above embodiment, the type of the battery 1 is a nickel-zinc secondary battery, but the present disclosure is not limited to this. The battery 1 may be, for example, a primary battery. Even in such a form, hydrogen is generated in the negative electrode 2 including the negative electrode current collector 20, and the hydrogen can be prevented from adhering to the outer surface 2a of the negative electrode 2.

[0074] The present disclosure is not limited to the above-mentioned embodiment, and can be realized in various configurations without departing from the spirit of the present disclosure. For example, the technical features of the embodiments corresponding to the technical features in each aspect described in the Summary of the Invention can be appropriately replaced or combined to solve some or all of the above-mentioned problems or to achieve some or all of the above-mentioned effects. Furthermore, if a technical feature is not described as essential in this specification, it can be appropriately deleted. [Explanation of symbols]

[0075] Reference Signs List 1...battery, 2...negative electrode, 2a...outer surface, 5...positive electrode, 8...electrolyte, 20...negative electrode current collector, 20a...current collector outer surface, 28...negative electrode active material, 50...positive electrode current collector, 58...positive electrode active material, 210...underlayer, 230...barrier layer, 250...alloy layer, 270...plating layer, C1...first separator, C2...second separator

Claims

1. A negative electrode current collector for a battery using an electrolyte, comprising: A base layer mainly composed of a conductive metal; a barrier layer formed on the underlayer and containing a transition metal as a main component; an alloy layer formed on the barrier layer and in which the transition metal and tin are alloyed; a plating layer containing tin as a main component and laminated on the alloy layer, the barrier layer contains at least one of boron, aluminum, phosphorus, titanium, and cobalt, which is a different element from the transition metal that is the main component of the barrier layer.

2. The negative electrode current collector according to claim 1 , The electrolyte is an alkaline aqueous electrolyte.

3. The negative electrode current collector according to claim 1 or 2, The negative electrode current collector, wherein the transition metal is at least one of nickel, iron, chromium, zirconium, and lanthanum.

4. The negative electrode current collector according to any one of claims 1 to 3, The negative electrode current collector, wherein the barrier layer has a thickness of 2 μm or more and 10 μm or less.

5. The negative electrode current collector according to any one of claims 1 to 4, The negative electrode current collector, wherein the plating layer has a thickness of 2 μm or more and 5 μm or less.

6. The negative electrode current collector according to any one of claims 1 to 5, The negative electrode current collector, wherein the plating layer further contains at least one element of indium and bismuth.

7. A battery, A negative electrode comprising the negative electrode current collector according to any one of claims 1 to 6 and a negative electrode active material; a positive electrode including a positive electrode current collector and a positive electrode active material; a separator separating the negative electrode and the positive electrode; a battery comprising: an electrolyte contained in a region in which the negative electrode, the positive electrode, and the separator are arranged.

Citation Information

Patent Citations

  • Alkaline zinc storage battery

    JP1986064078A

  • Zinc alkaline battery

    JP2005123176A

  • Copper foil for lithium secondary cell and its manufacturing method

    JP2009087561A

  • Tin and tin-zinc plated underlayers for performance improvement of nickel-zinc cells

    JP2010541183A

  • Negative electrode for lithium ion secondary battery and manufacturing method therefor

    JP2014107019A